Growth and Yield of Direct-Seeded Rice (Oryza sativa) as Influenced by Sowing Dates and Weed Management Methods - Mandal, Devendra; Kumar, Rakesh; Singh, Devendra; Kumar, Pramod (International Journal of Bio-resource and Stress Management, 2011)
A field experiment was conducted during rainy seasons of 2007 and 2008 at Rajendra Agricultural University, Pusa, Bihar on sandy loam soil to study the response of sowing date and weed management methods on direct seeded rice The treatments included sowing date before onset of monsoon (22nd June) and after onset of monsoon (12th July). The weed management methods were Pretilachlor-s 0.5 kg ha-1, Butachlor 1.5 kg ha-1 + 1 HW at 30 DAS, Fenoxaprop 60 g ha-1, Sesbania (broadcast) + 2,4-D 0.5 kg ha-1 along with weed free and weedy check. All the growth attributing characters viz. plant height, tillers m-1 row length , LAI, CGR, NAR and dry matter accumulation were significantly higher in plots getting weed free environment closely followed by pre-emergence application of butachlor 1.5 kg ha-1 + 1 HW. Weed population and weed dry matter was the least under weed free check followed by Sesbania broadcast + 2, 4-D and Butachlor + 1 HW. However, highest WCE (87%) was in weed free check followed by Butachlor + IHW (80%) and Sesbania broadcast + 2,4-D (76.5%), which had statistical equality between them